Midlife Lifestyle Activities Moderate APOE ε4 Effect on in vivo Alzheimer’s Disease Pathologies - Jeon, So Yeon; Byun, Min Soo; Yi, Dahyun; Lee, Jun-Ho; Ko, Kang; Sohn, Bo Kyung; Lee, Jun-Young; Ryu, Seung-Ho; Lee, Dong Woo; Shin, Seoung A; Kim, Yu Kyeong; Kang, Koung Mi; et al. (Frontiers in Aging Neuroscience, 2020)
This study aimed to investigate whether midlife cognitive activity and physical activity moderate the relationship between apolipoprotein E ε4 (APOE4) and in vivo Alzheimer’s disease (AD) pathologies. In total, 287 non-demented older adults (mean age 72 years) from the Korean Brain Aging Study for the Early diagnosis and prediction of Alzheimer’s disease cohort were included. Participants underwent a comprehensive clinical assessment including the evaluation for midlife CA and physical activity, [11C]-Pittsburgh-Compound-B-positron emission tomography (PET), [18F]-fluorodeoxyglucose PET, structural MRI, and APOE genotyping. We used linear regression and regression-based mediated-moderation models for statistical analyses. Neither midlife cognitive activity nor physical activity moderated the effect of APOE4 on β-amyloid (Aβ) retention itself. Midlife cognitive activity significantly moderated the effect of APOE4 on hippocampal volume [B (SE) = − 627.580 (252.327), t = −2.488, p = 0.014]: APOE4 carriers had smaller hippocampal volume than non-carriers at relatively high cognitive activity state (p = 0.004), but not at relatively low cognitive activity condition (p = 0.937). Midlife physical activity significantly moderated the effect of Aβ retention, which was closely related to APOE4, on AD-signature region cerebral glucose metabolism (AD-CM) [B (SE) = 0.004 (0.002), t = 2.030, p = 0.043]: Higher Aβ accumulation was associated with lower AD-CM in relatively low physical activity condition (p < 0.001), whereas no such association was observed in relatively high physical activity state (p = 0.791). The findings suggest that high midlife cognitive activity may accelerate hippocampal atrophy induced by APOE4, whereas high midlife physical activity may delay AD-related cerebral hypometabolism by weakening the influence of APOE4-associated Aβ retention.